2014
DOI: 10.1590/1413-7372189590001
|View full text |Cite
|
Sign up to set email alerts
|

Ser pai de filho surdo: da suspeita ao enfrentamento

Abstract: RESUMO. O presente artigo é um recorte de uma pesquisa que investigou as vivências de pais de filhos surdos. Neste texto, discutiremos, sob a ótica dos pais, os sentimentos envolvidos na significação da surdez de seus filhos, desde a suspeita até o enfrentamento. O estudo consiste de uma pesquisa qualitativa em que foram ouvidos cinco genitores que tinham filhos com diagnóstico de surdez. Para a coleta dos dados utilizou-se a entrevista semiestruturada, realizada individualmente. Os relatos foram gravados, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
7
0
8
Order By: Relevance
“…It is found that the couple feels lost after receiving the diagnosis, justifying the feelings of fragility and anguish. The preparation of professionals is essential for the family to be able to plan a future in the face of this new context (4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the couple feels lost after receiving the diagnosis, justifying the feelings of fragility and anguish. The preparation of professionals is essential for the family to be able to plan a future in the face of this new context (4) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the diagnosis of hearing impairment can be seen through a strong impact on the family, transforming family relationships, while disorder, conflicts and difficulties may occur due to possible communication problems among its members, requiring the participation of the entire family nucleus in the process of adaptation 1 . Furthermore, with the diagnosis of the child's hearing impairment problem, there is a transformation in the family relationship, in which the parents start to feel sorry for the child, sadness, guilt and helplessness, discomfort in the games, disappointment, among other feelings, while they go through the process of becoming aware of the situation lived at the time reflected (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Além do mais, ocorre uma grande quebra de expectativas, pois, normalmente, a família cria diversas idealizações a respeito do novo integrante da família, e após a notícia, ela encontra-se em um cenário novo, sendo necessário entende-lo para se ajustarem 13,15 . Diante desse cenário, cabe ao fonoaudiólogo, ouvir a família e conversar a respeito dos seus sentimentos em relação à DA, explicar todo o processo já realizado e o que ainda será, sanando todas as dúvidas 12,4 .…”
Section: Descriçãounclassified
“…"znieruchomienie", pasywność, bezsilność, słabość, poczucie kruchości, smutek, a także brak wewnętrznych zasobów do stawienia czoła nowej sytuacji i radzenia sobie z nią. Upływ czasu oraz interakcje z dzieckiem były ważnymi czynnikami, które przyczyniły się do powstania nowego znaczenia głuchoty i akceptacji dziecka przez ojców (Cortelo, Françozo, 2014).…”
Section: Wyzwania Wczesnej Diagnozy Uszkodzenia Słuchu U Dzieckaunclassified